-4=-x+3

Simple and best practice solution for -4=-x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4=-x+3 equation:


Simplifying
-4 = -1x + 3

Reorder the terms:
-4 = 3 + -1x

Solving
-4 = 3 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-4 + x = 3 + -1x + x

Combine like terms: -1x + x = 0
-4 + x = 3 + 0
-4 + x = 3

Add '4' to each side of the equation.
-4 + 4 + x = 3 + 4

Combine like terms: -4 + 4 = 0
0 + x = 3 + 4
x = 3 + 4

Combine like terms: 3 + 4 = 7
x = 7

Simplifying
x = 7

See similar equations:

| p=3+2p | | x/15-7=-2 | | -2n-23=4n+37 | | 3-5x-1/10=x-1/5-x-3/2 | | 1/3-1/8= | | X+8=-5x+20 | | t-5=-7+3t | | 20z-33=40 | | 4(2x+4)+2(3x-5)= | | 9d-1d+2d-9=4d | | 2xy+5x=63 | | Z/10-5=6 | | 23-16.6=x | | x*x=16.6 | | -5+7x=7x+5 | | -5+12=47 | | 8(-2+x)-4x=32 | | 1/12-2/3m=1/3 | | 2a+7=4a-2 | | -4f+5=f+9f+5 | | x*x=14.6 | | 4(a+5)-2(a-5)= | | 12(x+3)=4(2x+9)+7x | | 5x/3-4=2x/5 | | 6g+2(4g-3)+10=32 | | 5=y+9 | | -30=-5/3(x=25) | | m/-4=5=14 | | -7r+6=-15 | | 5x-18=6x+8 | | f(x)=6x^3-53x^2-11x+2 | | .35y=15 |

Equations solver categories